The success of biomaterial-based tissue engineering strategies for peripheral nerve regeneration - Jiang, Yuhui; Tang, Xiaoxuan; Li, Tao; Ling, Jue; Yang, Yumin (Frontiers in Bioengineering and Biotechnology, 2022)
Peripheral nerve injury is a clinically common injury that causes sensory dysfunction and locomotor system degeneration, which seriously affects the quality of the patients’ daily life. Long gapped defects in large nerve are difficult to repair via surgery and limited donor source of autologous nerve greatly challenges the successful nerve repair by transplantation. Significantly, remarkable progress has been made in repairing the peripheral nerve injury using artificial nerve grafts and a variety of products for peripheral nerve repair have emerged been approved globally in recent years. The raw materials of these commercial products includes natural/synthetic polymers, extracellular matrix. Despite a lot of effort, the desirable functional recovery still remains great challenges in long gapped nerve defects. Thus this review discusses the recent development of tissue engineering products for peripheral nerve repair and the design of bionic grafts improving the local microenvironment for accelerating nerve regeneration against locomotor disorder, which may provide potential strategies for the repair of long gaps or thick nerve defects by multifunctional biomaterials.